Flouting of Grice’s Maxim in Chris Rock ‘Selective Outrage’ Stand-Up Comedy Show on Netflix - Aura Febri Harvi (Universitas Negeri Medan, 2024)
This research aims to analyze the types and how flouting maxims are used in creating humor in Chris Rock's 'Selective Outrage' Stand-up Comedy Show on Netflix. It focuses on Chris Rock's stand-up comedy entitled Selective Outrage, which addresses social phenomena. It was nominated for a Golden Globe Award for Best Performance in Stand-Up Comedy on Television. The data was utterances displayed for 1 hour and 10 minutes in a script spoken or English subtitle in his comedy performance. The data was collected through a documentary method, using videos of Chris Rock's performance on Netflix. The study uses a descriptive-qualitative design to analyze the linguistic components of the material pragmatics in Chris Rock's comedy performances. The findings demonstrate that the comedian applies every type of maxim, including quality, quantity, relation, and manner to create humor, with maxims flout of quality being the most frequently used. The study also reveals that Chris Rock uses various strategies to flout his maxims, and irrelevant strategies are used more regularly than metaphor and understatement.